2017
DOI: 10.3390/molecules22111830
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia: A Gram-Negative Bacterium Useful for Transformations of Flavanone and Chalcone

Abstract: A group of flavones, isoflavones, flavanones, and chalcones was subjected to small-scale biotransformation studies with the Gram-negative Stenotrophomonas maltophilia KB2 strain in order to evaluate the capability of this strain to transform flavonoid compounds and to investigate the relationship between compound structure and transformation type. The tested strain transformed flavanones and chalcones. The main type of transformation of compounds with a flavanone moiety was central heterocyclic C ring cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…In the 1 H spectrum of synthetic compounds 3-9 were observed signals indicate a molecule with no substituent on the B ring; two methylene signals high-field region and two meta-substituted groups on the A ring and corresponding to the basic structure of a dihydrochalcone. In particular, the compound 3 was obtained as an white solid, proved to be identical to 2'-Hydroxy-4'-methoxydihydrochalcone, previously obtained as a biotransformation product of 7-methoxyflavanone by Stenotrophomonas maltophilia [21]. Moreover, compound 7 was obtained as a pale yellow solid in accordance with the data obtained previously for the molecule isolated from Lonchocarpus neuroscapha [24].…”
Section: Chemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…In the 1 H spectrum of synthetic compounds 3-9 were observed signals indicate a molecule with no substituent on the B ring; two methylene signals high-field region and two meta-substituted groups on the A ring and corresponding to the basic structure of a dihydrochalcone. In particular, the compound 3 was obtained as an white solid, proved to be identical to 2'-Hydroxy-4'-methoxydihydrochalcone, previously obtained as a biotransformation product of 7-methoxyflavanone by Stenotrophomonas maltophilia [21]. Moreover, compound 7 was obtained as a pale yellow solid in accordance with the data obtained previously for the molecule isolated from Lonchocarpus neuroscapha [24].…”
Section: Chemistrysupporting
confidence: 86%
“…In addition. this method of synthesis allows to obtain compound 2 with a good yield and in a short period of time; which for us has been excellent, because the reported yields do not exceed 4% both of natural origin or biotransformation product [19][20][21].…”
Section: Chemistrymentioning
confidence: 84%
“…Flavones used in biotransformations were synthesized from those substrates (the reactions are described below). The resulting chalcones were used as substrates for the flavone synthesis and their NMR spectral data are identical to those previously published [ 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 75%
“…All used substrates were synthesized in the laboratory by carrying out two kinds of reactions. Firstly five different methoxychalcones were synthesized in the Claisen-Schmidt reaction of 2-hydroxyacetophenone with suitable methoxybenzaldehyde in reaction, described earlier and shown in Scheme 2 [ 34 , 35 , 36 , 37 , 38 ]. The resulting flavones ( 1 – 5 ) were used as substrates for the biotransformation and their NMR spectral data are identical to those previously published [ 32 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The strains of the species Saccharomyces cerevisiae are widely described as biocatalysts, effectively reducing the double bond in various compounds – derivatives of chalcones [9], containing methyl, methoxy, hydroxy substituents [37], and even bromine or chlorine [33,38], in both A and B-rings. On the basis of the results obtained in this study, it can be concluded that a chalcone derivative, containing a heteroatom in the B-ring, is effectively transformed by this strain.…”
Section: Resultsmentioning
confidence: 99%